THE USE OF L1 AND L2 BY TEACHER IN EFL CLASSROOM AT JUNIOR HIGH SCHOOL IN PADANG - Adelia Nur Armadani; Yetty Zainil (Journal of English Language Teaching, 2018)
This is a descriptive qualitative and quantitative research which this research is aimed to investigate the percentage of mother tongue and second language by teachers in the classroom and their functions at the level of junior high school, especially in grade VII. Grade VII is chosen because of English is officially taught in Indonesia which means that English is very beginning level for junior high school student, especially in grade VII. This research is conducted in four junior high schools in Padang with teachers as the participants. These five teachers taught English in grade VII. Classroom observation and stimulated recall interview were used to look at the number of the language use by teachers, and the stimulated recall interview was used to clarify teachers` reasons of their language use. The result revealed that all the teachers use L1 and L2 in teaching English; they did code-switching in the form of translation. Another interesting finding is that all the teachers mentioned that they were not aware of their language use.Key words: code-switching, L1, and L2.